Melatonin Enhances Tomato Salt Tolerance by Improving Water Use Efficiency, Photosynthesis, and Redox Homeostasis - Chen Ru; Yuxuan Liu; Xingjiao Yu; Chuanliu Xie; Xiaotao Hu (Agronomy)
Salinity stress is a primary abiotic constraint limiting global crop productivity, with progressive soil salinization inducing growth inhibition and physiological dysfunction in plants. Although melatonin (MT) has been extensively documented to enhance stress adaptation, the underlying mechanisms through which it mediates salt tolerance by integrating physiological processes remain unclear. This study investigated the effects of varying MT concentrations on photosynthetic performance, plant water relations, water-use efficiency, and stress-responsive physiological parameters in tomatoes, aiming to identify the key physiological pathways for MT-mediated salt stress mitigation. The results showed that salt stress significantly reduced the leaf relative water content and root hydraulic conductivity, suppressed the photosynthetic rate, and ultimately caused significant reductions in the aboveground and root biomass. MT spraying effectively improved leaf water status and root water uptake capacity, enhancing the photosynthetic rate and water-use efficiency, thereby providing material and energy support for plant growth. Furthermore, MT spraying increased the total antioxidant capacity in leaves and promoted the synthesis of phenolic and flavonoid compounds, thereby reducing oxidative damage. Simultaneously, it stimulated the accumulation of osmolytes to enhance cellular osmotic adjustment capacity and optimized ion uptake to maintain cellular ion homeostasis. Among the tested concentrations, 100 μM MT showed the most significant alleviative effects. This concentration comprehensively enhanced the salt tolerance and growth performance of tomato plants by synergistically optimizing water use, photosynthetic function, antioxidant defense, and ion balance. In conclusion, these findings provide experimental evidence for elucidating the physiological mechanisms underlying MT-mediated salt tolerance in tomatoes and offer theoretical references for the rational application of MT in crop production under saline conditions.